Chloride-Binding Capacity of Portland Cement Paste Blended with Synthesized CA2 (CaO·2Al2O3). (25th March 2018) - Lee, Yunsu; Kim, Mingyun; Chen, Zhengxin; Lee, Hanseung; Lim, Seungmin
Abstract : A chloride-binding capacity is the major factor to mitigate the ingress of chloride into concrete. This paper presents the chloride-binding capacity of Portland cement paste containing synthesized CA2 (CaO·2Al2 O3 ). The CA2 was synthesized in the high-temperature furnace and characterized by X-ray diffraction for inspecting the purity. The synthesized CA2 was substituted for Portland cement by 0%, 5%, and 10% by weight, and the NaCl solution was used as an internal chloride, which is assumed as a total chloride. The chloride-binding capacity of cement paste was calculated from a water-soluble chloride extraction method by the application of the Langmuir isotherm equation. And the hydration products were analyzed using X-ray diffraction and thermogravimetric analysis. We demonstrate that the CA2 increases an AFm phase in the Portland cement system, and the incorporation of CA2 consequently enhances the chloride-binding capacity of cement paste samples.